“Where is the fun in eating without fat or salt?” A qualitative study on healthcare students, foodways, and dietary advice in Mexico - Tronco Hernandez, Yessica Abigail (2020)
Background: What to eat in order to maintain health is a controversial topic. Influences from our social context and contradictory messages affect society’s views, behaviours, and practices, especially in a time and context where diseases associated with diet are increasingly threatening the quality of life globally. As a result, gaining compliance and achieving health goals in patients is a challenge for future health professionals. Current evidence on food choices is mostly quantitative and has not sufficiently addressed questions of how and why people develop ‘foodways’, and the significance of healthcare students (HS) foodways in practice.